III SBC Guidelines on the Analysis and Issuance of Electrocardiographic Reports - Executive Summary - Pastore,Carlos Alberto (2016)
Abstract The third version of the guidelines covers recently described topics, such as ion channel diseases, acute ischemic changes, the electrocardiogram in athletes, and analysis of ventricular repolarization. It sought to revise the criteria for overloads, conduction disorders, and analysis of data for internet transmission.